Water mite diversity from southwestern Türkiye through the lens of the DNA barcodes, with the description of one new species (Acari, Hydrachnidia) - Vladimir Pešić; Andrzej Zawal; Pınar Gülle; İskender Gülle; Milica Jovanović; Aleksandra Bańkowska; Stanisław Musielak; Harry Smit (ZooKeys)
This study presents the molecular and morphological results from an analysis of water mites collected in southwestern Türkiye. 83 COI barcodes are provided, clustered into 40 BINs, with 23 BINs being unique and deposited for the first time in the Barcode of Life Data Systems (BOLD). The first DNA barcodes for eight water mite species are uploaded into the BOLD database. In total, 34 water mite species were identified and one of them, Iranothyas marismortui (Gerecke, 1999) is newly reported from Türkiye. Iranothyas alhajarica Pešić, Gerecke & Smit, 2009 is excluded from the fauna of Türkiye. Sperchon fundamentalis Bader & Sepasgozarian, 1980, a species previously synonymized with S. glandulosus Koenike, 1886 is resurrected as a valid species. One species, Atractides turani Pešić, Zawal, Gülle & Smit, sp. nov. (Hygrobatidae), is described as new to science.